(untitled) (World Bulletin of Education and Learning, 2025)
This article presents a theoretical and practical presentation of a modern methodological model for training educators. It focuses on developing the professional competence, moral and spiritual maturity, and practical skills of future teachers, combining the purpose, content, form, and methods of pedagogical activity.